Une analyse des discours sur le rôle d’une expérimentation dans la production urbaine : le projet Darwin à Bordeaux - Sandra Mallet; Arnaud Mège (Développement Durable et Territoires)
The article analyzes the speeches made about the Darwin Ecosystem in Bordeaux, revealing, in our opinion, different ways of understanding and thinking about the issue of experimentation in the ecological transition. The project is conceived as a hybrid place, combining accommodation for SSE project leaders, cultural associations and businesses, in an approach that aims to be exemplary in terms of sustainable development.Both private and partly occupied without right or title, Darwin strongly questions the place and role of this type of alternative in the city, especially in view of the conflict that has opposed it for several years to the developer of a ZAC. Darwin appears as a revelation of the tensions between a desire to « do the city differently », in a more flexible and resilient manner, and models that are still dominant, characterized by large-scale projects that are difficult to adapt to change, directly questioning the capacity of urban planning actors to integrate this type of initiative into their projects in the long term.